Mao’s Ordinary People - Thornton, P (Current History, 2016)
This year marks the fiftieth anniversary of the Cultural Revolution’s launch. In China, substantive public discussion of the subject remains taboo. The official line of the Communist Party (CCP), circulated in 1981 in the form of a resolution on party history, pronounced the entire decade from 1966 to 1976 as a cataclysmic leftist error initiated by Mao Zedong that resulted in “the most severe setback and the heaviest losses suffered by the party, the state, and the people since the founding of the People’s Republic.” Despite the party’s unequivocal condemnation of the movement, backed up by a highly efficient censorial regime, Chinese authorities have been on high alert since the beginning of this year. As early as March, the party tabloid Global Times warned its readership that “small cliques” might exploit the anniversary to circulate “chaotic misunderstandings” of the Cultural Revolution. Loyal party members were instructed to remain vigilant, and not to depart or deviate in any way from the official determination on the matter, lest either popular discussion or scholarly reflection on this critical watershed in twentieth-century Chinese politics challenge the party’s final word. Fortunately, however, scholars based outside of the People’s Republic in recent years have availed themselves of a wide variety of materials to provide us with new understandings and fresh perspectives on the period.